ANALISIS FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH PROGRAM STUDI PG-PAUD FKIP UNIVERSITAS RIAU - Santoso, Dessya Liana; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the factors that influence students to choose Study Program of Early Childhood Teacher Education Faculty of Teaching and Education University of Riau. The population in this research is active student of Study Program of Early Childhood Teacher Education Faculty of Teaching and Education University of Riau force of 2013, 2014, 2015, and 2016 which amounted to 356 people, this sample of 155 students is taken by using technique Proportional Stratified Random Sampling with 10% error rate. The method used is Factor Analysis with Exploratory factor analysis (EFA) to know the factors that influence the students to choose Study Program of Early Childhood Teacher Education Faculty of Teaching and Education University of Riau. Data collection techniques used are questionnaires in the form of Likert scale. Data analysis techniques use scale test and statistical method analysis with IBM SPSS Statistic Ver.23 program. Based on the results of data analysis and discussion there are 7 factors that influence the students to choose the Study Program of Early Childhood Teacher Education Faculty of Teaching and Education University of Riau, namely: (1) Lecture Process Factor, (2) Self Motivation Factor, (3) Prospect Factor Career, (4) Talent and Interest Factor, (5) Social Status Factors, (6) study program enthusiasts factor, (7) Facilities and Infrastructure Factors. Keywords: Factor Analysis, Selection of Study Program,Early Childhood Education